If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 75 + -9n = 0 Solving 75 + -9n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-75' to each side of the equation. 75 + -75 + -9n = 0 + -75 Combine like terms: 75 + -75 = 0 0 + -9n = 0 + -75 -9n = 0 + -75 Combine like terms: 0 + -75 = -75 -9n = -75 Divide each side by '-9'. n = 8.333333333 Simplifying n = 8.333333333
| p/14=1 | | -20=k-19 | | 10x-16=8x+7 | | -54=9h | | 4b+2=9b-23 | | 0.28y+8=11 | | 3(6x-5)=18x+15x | | b/17=-13 | | 4(x-30)+5x=-48 | | x+(1+x)+(2+x)=228 | | 5r-4r=16 | | -8(9h-5)=-17 | | -12+4n=4 | | -11+b=-3 | | 19a-12-4a=(-57) | | (Y6/Y3)4 | | k/18=-4 | | 393=17n+2 | | 13=11-y | | m/15=16 | | -6x-10=-16 | | -5d-24=4(1d+6)-1d | | 6x+21=6x+24-3 | | 2(2z-3)-2(4-5z)=2 | | -50x^10/10x^5 | | -5-3x=25 | | 2m-8=6 | | 3a^2+10=0 | | 5x(x-3)+6=5x-9 | | m+-1=9 | | 6x+6.32=2x+14 | | -5s-16=-4s |